Wordwall Interactive Game Media in Natural Science Lessons for Class V Primary School (Current Research in Education: Conference Series Journal, 2024)
The research was conducted with the aim of creating learning facilities intended to: (1) develop interactive learning media for science lessons for fifth grade elementary school, (2) evaluate the relevance of use interactive learning media in science lessons in class V elementary school, (3) describing students' interest in wordwall media based on online games in thematic learning of science content in class V elementary school. Study use ADDIE method which has five stages study namely analysis, design, development, implementation, evaluation. Initial product development consists of media expert validation and material expert validation. The result is that the development of Wordwall media at the user stage gets very good results.